Alternatif Kebijakan Operasional Program Pencegahan Anemia Remaja Puteri di Kabupaten Garut - Rosita Alvia; Astrid Novita (Jurnal Medika Cendikia, 2018)
The prevention of youth anemia is one of the efforts to lower the maternal mortality rate, Understanding the prevention of adolescent anemia is very important because the teenager is a budding mother. Policy of prevention anemia in young women are regulated in UU No. 36 of 2009 on Health Article 142 victims of violence committed in all life cycles with priority in nutrition prone groups, namely infants, young women, pregnant and lactating wome. This study aims to find out alternative operational policy of prevention anemia in young women in Garut regency Year 2017; To analyze the problem of the operational policy of the prevention program of anemia in the adolescent girl in Garut regency in 2017; Analysis of criteria for anemia prevention Program for adolescent girls in the regency Garut in 2017; To provide an alternative recommendation for anemia prevention Program for adolescent girls in the regency Garut in 2017.This research method is qualitative with case study, Technique of taking observation data, detailed interview with 19 persons and literature study. The results of the study found three policy alternatives that can be applied to the prevention of adolescent anemia in Regency Garut, the third policy is: (i) Create standard operational procedures; (ii) Develop promotional media; (iii) Proposed of training for health center to SDK, subsequently conducting alternative assessments selected and based on CSF which is an alternative priority is to make and socialize SOP for Prevention of Anemia of Puteri Girls in Garut Regency, SOP is made and reviewed by some competent experts who are in Health Office and Puskesmas, then revised and legalized by the Puskesmas and socialized to program implementers at the Puskesmas. District Health Office Garut is expected to provide training anemia prevention for adolescent girls to program implementers and develop promotional media about anemia prevention for adolescent girls.